Developing an instrument to evaluate the influential factors of the success of local curriculum - Dedek Andrian (Program Pascasarjana Universitas Negeri Yogyakarta & HEPI, 2019)
The purpose of this study is to create an instrument to evaluate the factors that influence the success of the local curriculum in senior high school. The instrument developed is essential to find out what factors influence the success of the local curriculum. This research is a research and development which consists of three stages: (1) initial investigation, (2) design and validation stages, (3) trials, evaluations, and revisions. The results of small scale trials were analyzed using EFA (Exploratory Factor Analysis), obtaining one invalid item from 32 items. The results of a wide-scale test analyzed using CFA (Confirmatory Factor Analysis) obtained all indicators have loading factors 0.3 and reliability constructs 0.7. The results of the analysis show that the developed instrument fits the data obtained in the field. From the constructs of the instrument development, it is indicated that there are nine influential factors, consisting of regional government support, local community support, local industry support, academic community support, student interest, student motivation, practical tools, practical materials, and funds to buy lab material. The instrument developed has been used properly to obtain information about the factors that influence the success of the local curriculum.